Mild head injury in children : incidence, etiology and neuropsychological sequelae : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University - Broome, Erika Leigh (Massey University, 1998)
The present study examined the incidence, etiology and neuropsychological sequelae of head injury in an Intermediate School aged sample (11-13 years). The study was conducted in two parts. The first part examine the incidence, etiology and awareness of the consequences of head injury, this information was obtained thorough the screening questionnaire. Of the 173 participants who completed the questionnaire, 41% (42 males and 29 female) reported that they had sustained a head injury, of these, 33.8% reported sustaining more than one injury. In line with the current research, the majority of the head injuries sustained were mild. The gender difference observed in the literature were also reported in the present study, in that males not only sustained more head injuries than females, with a ratio of 1: 1.4, they also sustained more severe injuries. Sport was found to be the most common cause of head injury, with those reporting a head injury playing significantly more hours of sport per week than those who had not sustained an injury. And finally, the level of awareness of the symptoms of head injuries was investigated and it was found that those who had sustained a head injury were more aware of the consequences than the participants who had not sustained a head injury. For part two of the study, 43 participants (24 with head injury and 19 controls) were selected to complete a variety of neuropsychological measures and behavioural rating questionnaires. The measures selected were reported to be sensitive to the effects of mild head injury and assessed long and short term memory, attention, concentration, information processing and learning. The results showed that the only statistically significant differences between the head injury and control groups were on the Interference Trial and Trials 6 and 7 of the Auditory Verbal Learning Test. In conclusion, it was found that head injury and multiple head injuries are prevalent in this age group, with the majority of injuries being light or mild. With respect to gender differences and the etiology of head injuries the findings in the present study are in line with current trends. However, small sample sizes meant that comparisons of neuropsychological functioning could not accurately be made between the severity of injuries and the number of injuries.
Keywords: Head injuries; School children, New Zealand; Neurological functioning; Injuries at school; School head injuries